The Influence of Leadership, Motivation and Work Discipline on Employee Performance Directorate of Vocational High Schools, Ministry of Education and Culture Office - Surya Parlinanta, Tri; Pujiati, Herni (Dinasti Publisher, 2025)
This study aims to determine the effect of leadership, motivation, and work discipline on employee performance at the Directorate of Vocational High Schools by using the SPSS test. The data analysis method in this study uses a quantitative approach with quantitative data processing techniques using multiple regression analysis. The data collection technique used was a questionnaire. The questionnaire was distributed to employees of the Directorate of Vocational High Schools. Measurement is done with Likert on a scale of one to five. The results of this study indicate that if from the t test it can be seen that the result of the t value is 2.402> 2.0129 or the Sig value of 0.020 <0.05, meaning that the leadership variable greatly affects the performance of employees of the Directorate of Vocational High Schools. Judging from the t test, it can be seen that the result of the t value is 2.177> 2.0129 or the Sig value of 0.035 <0.05, meaning that the motivation variable greatly affects the performance of employees of the Directorate of Vocational High Schools. Judging from the t test, it can be seen that the result of the t value is 2.408> 2.0129 or the Sig value of 0.020 <0.05, meaning that the motivation variable is very influential on the performance of employees of the Directorate of Vocational High Schools. Meanwhile, judging from the F test, it can be seen that the significance value of Leadership X1, Motivation X2, and Discipline X3 on employee performance Y is 0.000 <0.05 and F count 66.820> 2.80, it cannot be denied because H0 is rejected, so it can be concluded that Leadership, Motivation and Discipline affect employee performance.